2011
DOI: 10.1016/j.ijcard.2011.09.072
|View full text |Cite
|
Sign up to set email alerts
|

Exercise oscillatory ventilation reflects diminished quality of life and perceived functional capacity in patients with heart failure

Abstract: A significant number of patients with heart failure (HF) present with both diminished self-reported quality of life and perceived functional capacity. The Minnesota Living with HF Questionnaire (MLWHFQ) and the Duke Activity Status Index (DASI) are two validated and reliable tools that have been frequently used to quantify quality of life and functional capacity in this chronic disease population [1,2]. Previous research by our group has demonstrated that peak oxygen consumption (VO 2 ) is significantly correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…As changes in the complex exercise response are caused by the central nervous system [48], one specific explanation for the initiation of EOV cannot be pointed out at this moment. Therefore, it might be assumed that low daily physical activity [18,33] and/or quality of life in general could be a warning signal for the presentation of EOV in an early stage of the disease [49]. The fact that EOV also appears in other populations such as liver transplant patients [50] supports this idea.…”
Section: Discussionmentioning
confidence: 99%
“…As changes in the complex exercise response are caused by the central nervous system [48], one specific explanation for the initiation of EOV cannot be pointed out at this moment. Therefore, it might be assumed that low daily physical activity [18,33] and/or quality of life in general could be a warning signal for the presentation of EOV in an early stage of the disease [49]. The fact that EOV also appears in other populations such as liver transplant patients [50] supports this idea.…”
Section: Discussionmentioning
confidence: 99%
“…A recent metaanalysis suggested that the prevalence of EOV in subjects with heart failure depends upon the definition applied . As a result, the reported prevalence of EOV in heart failure patients ranges from 7% to 64% (Olson et al 2008, Arena et al 2011. Furthermore, found different interpretations regarding the mathematical terms and characteristics within an applied definition; different interpretations of oscillatory cycle length, duration of cycle length, total oscillatory duration, and amplitude .…”
Section: Discussionmentioning
confidence: 99%
“…EOV has been shown to be a strong predictor of mortality in HFrEF [1][2][3]. In this setting, prevalence is widespread, ranging from 7 to 51% [16][17][18][19][20][21][22][23][24][25][26][27][28]. The variance of EOV might originate from the heterogeneity of its definition and different techniques of measures [29]: four original EOV descriptions [10,17,26,29] have been rec-ommended but many modifications are allowed.…”
Section: Discussionmentioning
confidence: 99%